2016
DOI: 10.1016/j.bpj.2015.11.2380
|View full text |Cite
|
Sign up to set email alerts
|

The β4 Subunit of L-Type Ca2+ Channels Regulates Transcription of Antiviral Factors in a Heart Cell Line

Abstract: Integrator 1 (BIN1), in the clustering of Ca v 1.2 channels in ventricular myocytes. Both of these proteins are known to directly interact with Ca v 1.2 channels. AKAP150 is important for local membrane targeting of PKA, PKCa and calcineurin, while Bin1 has established roles in cardiac t-tubule folding and in the trafficking and localization of Ca v 1.2 channels to t-tubules. Using GSD superresolution imaging, we found that clustering of Ca v 1.2 channels in these cells is unaltered by genetic ablation of AKAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We previously showed that these cells are susceptible to infection by dengue virus (DENV) (23), a single-stranded positive RNA virus of the Flaviviridae family, the pathogenic agent that causes dengue fever, which can damage the heart, liver, lungs, and other organs and is potentially fatal (24)(25)(26). Previous work showed that Ca 2+ homeostasis is disturbed by viral proteins (27,28). Furthermore, increased [Ca 2+ ] i has been observed in skeletal muscle cells from DENV-infected patients (25), and critical virus-host interactions depend on cellular Ca 2+ -regulated proteins; however, the involvement of Ca v 1.2 channels in viral infection of the heart is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that these cells are susceptible to infection by dengue virus (DENV) (23), a single-stranded positive RNA virus of the Flaviviridae family, the pathogenic agent that causes dengue fever, which can damage the heart, liver, lungs, and other organs and is potentially fatal (24)(25)(26). Previous work showed that Ca 2+ homeostasis is disturbed by viral proteins (27,28). Furthermore, increased [Ca 2+ ] i has been observed in skeletal muscle cells from DENV-infected patients (25), and critical virus-host interactions depend on cellular Ca 2+ -regulated proteins; however, the involvement of Ca v 1.2 channels in viral infection of the heart is unclear.…”
Section: Introductionmentioning
confidence: 99%